A6.17 Fra-1: Dr Jekyll or Mr Hyde for the resolution of inflammation in rheumatoid arthritis. (13th February 2015) - Hannemann, N; Schleicher, U; Bogdan, C; Baum, W; Schett, G; Bozec, A
Abstract : One feature of the AP-1 transcription factor family is their ability to regulate inflammatory processes and the activation and formation of osteoclasts. To test whether AP-1 expression is involved in rheumatoid arthritis (RA), serum K/BxN transfer model (SIA) is used. At the molecular levels, AP-1 expression analyses in wildtype joints show increased Fra-1, Fra-2 and cFos mRNA levels after SIA, whereas these Fos members are decreased in Fra-1 fl/fl MxCre + mice after SIA, suggesting that Fra-2 and cFos expression are Fra-1 dependent. In addition, despite a similar rise of the disease in Fra-1deficient mice and wildtype littermates, Fra-1 deleted mice show a faster resolution of the disease than littermate controls, with lower inflammation area, bone erosion and osteoclast number. The pro- and anti-inflammatory cytokines profiling in the joints reveal a decreased TNF and increased IL-10 levels in Fra-1deletedmice compared to littermate controls. Moreover, knowing the essential actions of macrophages (Mφ) in joint destruction and remodelling, the expression of Mφ-specific molecules CD11c, CD206 and Arginase-1 (Arg-1) were analysed. Interestingly, CD206 and CD11c mRNA levels were decreased, whereas Arg-1 expression was highly increased in Fra-1 fl/fl MxCre + joints compared to wildtype littermates, suggesting an alteration of Mφ polarisation in Fra-1 mutant mice. Indeed, in vitro stimulation of Fra-1 deleted Mφ with LPS and apoptotic cells, confirmed that (i) Fra-2 and cFos expression were Fra-1 dependent and that (ii) absence of Fra-1 altered Mφ polarisation, reaffirming the essential role of Fra-1 in pro-inflammatory Mφ activation. Finally, we found that Fra-1 can directly binds and regulates CD206, CD11c and Arg-1 promoters, and thereby regulates Mφ differentiation in RA. In conclusion, our data describe a new role of Fra-1 in Mφ activation in the maintenance of inflammation and joint destruction during acute RA.